Selling to China Stories of Success, Failure, and Constant Change - Gibbs, Ker D. (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
"Selling to China is good - really good. The down to earth advice from American business people in today's uncertain political environment is excellent! It's factual, honest, and nuanced. A must read for anyone who wants to understand China's new business environment." - Max Baucus, U.S. Ambassador to China (2014-2017), and U.S. Senator (1978-2014) "Selling to China is about U.S.-China relations but it's important for European businesses too. This is a practical handbook written by active business people with on-the-ground management experience." - Jörg Wuttke, President, European Union Chamber of Commerce in China "These business executives share their experiences in an attempt to inform the public and the policy-making community about a complicated but ultimately mutually beneficial relationship. There is no more important read than this book at this time." - Professor Scott Rozelle, Stanford University This book, edited by the immediate past president of the American Chamber of Commerce in Shanghai, is about the opportunities and challenges facing foreign companies operating in China. It includes stories about 3M pivoting to find new market opportunities, and a single tweet about pro-democracy protests in Hong Kong that nearly shuttered the NBA in China, leading to hundreds of millions in lost revenue. The United States and China seem locked in conflict, but readers may be surprised to learn how well many American businesses have been doing in what is the largest growth market in the world for many products. Today, GM sells more cars in China than in the United States; Tesla also does well but faces intense competition from Chinese EV makers. Selling to China is a collection of essays written by C-suite executives managing foreign companies in China. Each brings a unique perspective and explains the issues in a different industry. The editor, Ker Gibbs, first came to China in 1985 and worked in banking, consulting, and other roles giving him broad exposure to U.S.-China relations and issues American companies face in Asia.
Introduction: In China Selling to China: How foreign business managers view life and work in a country taking its own path -- Chapter 1 Sports marketing and media -- Chapter 2 China's Auto Industry and the Race to a Sustainable Future -- Chapter 3 Digital Marketing in China -- Chapter 4 Manufacturing and Supply Chain -- Chapter 5 Industrial and Diversified Industries -- Chapter 6 Industrial and Consumer Business.
Keywords: Asia -- Economic conditions; Business; Management science; International economic integration; Globalization; Asian Economics; Business and Management; Economic Aspects of Globalization